Vocational training of experts in system of art-pedagogical education (a problem experience) (Pedagogy of Higher and Secondary Education, 2006)
The questions of scientific orgamzaBon of art pedagogical pnparanon of future teachers of fine arts ar considered.
Keywords: educational process; preparation of teachers